Multi-hazard Early Warning for All Action Plan for Africa (2023-2027) - World Meteorological Organization; United Nations Office for Disaster Risk Reduction; African Union; International Telecommunication Union; International Federation of Red Cross and Red Crescent Societies (2023)
The Early Warning for All (EW4All) Action Plan is a comprehensive initiative in Africa aimed at improving early warning systems across the continent to enhance disaster preparedness and response. The initiative outlines the key objectives, strategies, and expected outcomes. The primary objective of the initiative is to strengthen early warning systems in Africa, ensuring that timely and accurate information about natural hazards and impending disasters reaches all segments of society, particularly the most vulnerable populations. This follows the UN Secretary General call that seeks to ensure that every person worldwide is protected by early warning systems by 2027. The Action Plan is anchored on existing continental strategies and initiatives to build resilience that include the Africa Regional Strategy for Disaster Risk Reduction, the Programme of Action for the implementation of Sendai Framework 2015-2030 in Africa, the Africa Climate Change and Resilient Development Strategy and Action Plan 2022- 2032, the Revised Integrated Africa Strategy for Meteorology (Weather and Climate Service), Action on Water Adaptation and Resilience (AWARe), among others. It aims to support the implementation of the EW4All initiative in Africa and to also strengthen the operationalization of AMHEWAS to bridge existing gaps and establish continent-wide early warning systems coverage by 2027. EW4All Action Plan is fully aligned with Agenda 2063, ‘The Africa we want’, the Africa Climate Change Strategy, the 2030 global agenda and supports key Sendai Framework for Disaster Risk Reduction provisions and the Paris Agreement on climate change and the Sustainable Development Goals on poverty, hunger, health, water, clean energy, climate action and sustainable cities.